A decomposition theorem for fnite‐dimensional Jordan superalgebras whose simple part is Kan(2) (2023)
ABSTRACT: We consider a fnite-dimensional Jordan superalgebra A over a feld of characteristic zero F such that N is the solvable radical of A. We proved that if N 2 = 0 and A∕N is isomorphic to simple Jordan superalgebra of Grassmann Poisson bracket Kan(2), then an analogous to Wedderburn Principal Theorem (WPT) holds.